2017
DOI: 10.1111/jnc.14005
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin attenuates amyloid beta‐induced inflammatory and pro‐oxidant responses in astrocytes and microglia

Abstract: Alzheimer's disease (AD) is characterized by extracellular senile plaques, intracellular neurofibrillary tangles, and neuronal death. Aggregated amyloid-β (Aβ) induces inflammation and oxidative stress, which have pivotal roles in the pathogenesis of AD. Hepcidin is a key regulator of systemic iron homeostasis. Recently, an anti-inflammatory response to hepcidin was reported in macrophages. Under the hypothesis that hepcidin mediates anti-inflammatory response in the brain, in this study, we evaluated the puta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 73 publications
3
45
0
Order By: Relevance
“…A microglia‐conditioned media system was used as previously described . BV2 cells were plated in 6‐well culture plates at a density of 2 × 10 5 cells/well.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A microglia‐conditioned media system was used as previously described . BV2 cells were plated in 6‐well culture plates at a density of 2 × 10 5 cells/well.…”
Section: Methodsmentioning
confidence: 99%
“…A microglia-conditioned media system was used as previously described. 18 BV2 cells were plated in 6-well culture plates at a density of 2 × 10 5 cells/well. After overnight incubation, the cells were pretreated with different concentrations of BAI for 1 hour followed by stimulation with 10 μmol/L Aβ 1-42 and 1 μg/mL LPS for 24 hours.…”
Section: Microglia-conditioned Media Systemmentioning
confidence: 99%
“…It has been shown previously that amyloid beta treatment of astrocytes increases the levels of inflammatory cytokines [27]. Here we examined whether sinomenine affects the production of inflammation-related molecules from ADDL-treated astrocytic cells.…”
Section: Sinomenine Inhibits Amyloid Beta-induced Increase In the Levmentioning
confidence: 94%
“…The fact that LPS and E. coli infection upregulates the levels of hepcidin mRNA and/or protein in the brain shows that HAMP gene expression can also be upregulated by inflammation, as was found outside of the brain. The finding that pretreatment with hepcidin reduces Aβ treatment‐induced IL‐6 expression and secretion in astrocytes and microglia and reduces neurotoxicity and oxidative damage triggered by conditioned media obtained from Aβ‐treated astrocytes and microglia imply that hepcidin can downregulate inflammatory and prooxidant processes . Recent studies have also demonstrated that intracerebroventricular injection of LPS can upregulate hepcidin expression and also downregulate Fpn1 levels in the cortex and substantia nigra of the rat brain.…”
Section: Hepcidin and The Treatment Of Neurodegenerative Disordersmentioning
confidence: 99%